Incidencia de los procesos de contratación pública en la gestión de la dirección distrital de salud 09d15 El Empalme, año 2022. - Llerena Ureta, Jesenia Fernanda (2023)
The objective of this research is to analyze public administration and its effect on the hiring processes of the District Health Directorate 09D15 El Empalme, year 2022. For the development of the theoretical framework, it was necessary to review academic contents represented as a secondary source, the information was collected scientific articles published in indexed journals, research methodology books, specialized books on the development of educational processes, doctoral and master's theses. The types of research used were descriptive research and explanatory research, as part of the research methods the inductive, deductive, analytical and synthetic method was used. The study population of this research was made up of the administrative staff of the District Health Office 09D15 El Empalme. The interview technique was applied, the same one that was generated to the District Health Director 09D15 El Empalme, the instrument for the collection of information is represented by a semi-structured questionnaire with open questions, the same one that had the accompaniment of a voice recorder and note-taking, which allowed the information of the interviewee to be archived in real time. A Census was prepared with open option questions, the same one that was applied to the administrative staff. Exposing how a series of questions to be analyzed by the administrators results, as well as the way in which the district’s resources are managed, several guides to substantially improve the Institutional objectives of this health center and additional parameters to optimize their services in general.